Exploring library disaster management preparedness and responses in Malaysian academic libraries / Mohd Ismail ... [et al.] - Ismail, Mohd; Mohamed Shuhidan, Shamila; K, Kiran; SF, Samsuddin (Faculty of Information Management, 2023)
Disaster management, whether natural, man-made, or health-related, is integral to library management. The purpose of this paper is to investigate the preparedness and response of academic libraries to the disruption of library services during the Covid-19 pandemic. This paper presents qualitative findings from multiple case studies conducted at academic libraries in Malaysia. The data were subsequently subjected to thematic analysis. The results disclose how Academic Libraries expanded/modified their public service policies in response to the disaster, particularly the Covid-19 pandemic. Changes in roles in the provision of services and facilities that are more necessary during a disaster are shared by library managers and can serve as benchmarks for other libraries to implement as necessary. Academic libraries in Malaysia are perceived to have a strategy and their own plans to respond to a disaster crisis, but they lack a formal disaster management plan. This study's findings provide several significant practical contributions for library professionals to ensure the continuity of their services in the event of a disaster. It can also serve as a baseline for policymakers preparing disaster response policies, guidelines, or manuals.